Effectiveness of health services through the mobile-JKN application for the elderly: A case study at the Gunung Tua BPJS health office, North Sumatra - Siregar, Hikmah; Nasution, Annio Indah Lestari; Qarni, Waizul (Institute of Computer Science (IOCS), 2026)
This study aims to analyze the effectiveness of healthcare services delivered through the Mobile JKN application for elderly participants at the BPJS Kesehatan Gunung Tua Office, North Padang Lawas Regency. A descriptive qualitative approach was applied, with data collected through interviews, observations, and literature review. The findings indicate that the utilization of Mobile JKN among the elderly has not yet reached an optimal level due to low digital literacy, limited smartphone ownership, unstable internet access, and difficulties in using application features. Family support plays a crucial role in improving service effectiveness, particularly through assistance from children or grandchildren in accessing digital services. Based on the SERVQUAL dimensions, Mobile JKN shows adequate reliability and empathy but still requires improvement in interface simplicity, responsiveness, and accessibility for elderly users. Overall, Mobile JKN has strong potential to enhance healthcare service efficiency if supported by continuous socialization, digital literacy strengthening, improved infrastructure, and family-based assistance.